2018
DOI: 10.1021/acs.analchem.8b03969
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Sensor for Carbonyl Groups in Oxidized Proteins

Abstract: The interaction of proteins with free radicals leads, among other types of damages, to the production of stable carbonyl groups, which can be used as a quantification of oxidative stress at proteins level. The aim of this study was the development of an electrochemical sensor for the detection of carbonyl groups in proteins oxidized by reactive oxygen species. Its working principle is based on the redox properties of dinitrophenylhydrazine (DNPH). BSA was used as a model protein and its oxidation achieved thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 35 publications
(51 reference statements)
0
4
0
Order By: Relevance
“…Compared with traditional detection methods such as fluorescence, the use of electrochemical biosensors has gained widespread attention in marker detection due to their high sensitivity and ease of operation, 6,7 but they still face challenges in the detection of low abundance ExoPD-L1. Advances in nanotechnology have enabled nanomaterials to show outstanding advantages in highly sensitive detection of electrochemical biosensors.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with traditional detection methods such as fluorescence, the use of electrochemical biosensors has gained widespread attention in marker detection due to their high sensitivity and ease of operation, 6,7 but they still face challenges in the detection of low abundance ExoPD-L1. Advances in nanotechnology have enabled nanomaterials to show outstanding advantages in highly sensitive detection of electrochemical biosensors.…”
Section: Introductionmentioning
confidence: 99%
“…[5]. This pathological or physiological process generates certain electroactive molecules known as biomarkers via hydroxylation, nitration [6], oxidative deamination (reactive carbonyl moiety) [7], and free radical chain oxidation (O 2 addition to carbon radicals; fragmentation of peroxyl radical) [8] reactions. Oxidative stress can be diagnosed by monitoring oxidation adducts of DNA, proteins, lipids, the activity of enzymes, and antioxidants status [9,10] (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…Until the end of 1980s, it was already demonstrated that the redox properties of amino acids, especially Tyr and Trp, allow the investigation of proteins [ 1 , 2 ]. The last decade came with the elucidation of electroactive amino acids oxidation mechanisms [ 5 , 6 , 7 , 8 , 9 ], while the research was extended to broad studies regarding different phenomena such as adsorption [ 9 ], aggregation [ 10 ], fibrilization [ 11 ], structural modifications [ 12 ], protein/enzyme–substrate interaction [ 13 ], etc., and the investigation addressed to peptides [ 14 ], amyloids [ 15 , 16 ], proteins [ 15 , 17 ], and enzymes [ 14 ]. At the same time, in the last decade, this field of electrochemistry has been governed by the use of glassy carbon working electrodes [ 18 ] and other carbon electrodes, such as disposable carbon-based screen-printed electrodes [ 19 ], mainly due to their broad potential window, which is usual between −1.0 V and +1.4 V [ 18 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%